Writing strategies used by Malaysian ESL undergraduates / Lee Lai Fong … [et al.] - Lee, Lai Fong; Teoh, Sian Hoon; Narayanan, Geethanjali; Kaur Sidhu, Gurnam; Chan, Yuen Fook (Penerbit UiTM (UiTM Press), 2015)
Writing strategies are deemed important to enable learners to write well in academic contexts in higher education. This study examined the writing strategies of English as Second Language (ESL) undergraduates in higher education to look into the type of writing strategies they use. The five categories of writing strategies focused on were rhetorical strategies, metacognitive strategies, cognitive strategies, communicative strategies, and social/affective strategies. The sample of this study comprised 40 students from the social science disciplines in a local public university. The instrument used to collect data was questionnaire. The results showed that the students used all five categories of writing strategies. However, metacognitive strategies, cognitive strategies as well as social/affective strategies were used slightly more compared to communicative strategies and rhetorical strategies. This study has implications for ESL student writers and instructors on writing strategies that can be used to facilitate academic writing